Original paperThe relationship between neutrophil to lymphocyte ratio, platelet to lymphocyte ratio and thrombolysis in myocardial infarction risk score in patients with ST elevation acute myocardial infarction before primary coronary intervention - Acet, Halit; Ertaş, Faruk; Bilik, Mehmet Zihni; Akıl, Mehmet Ata; Özyurtlu, Ferhat; Aydın, Mesut; Oylumlu, Mustafa; Polat, Nihat; Yüksel, Murat; Yildiz, Abdulkadir; Kaya, Hasan; Akyüz, Abdurrahman; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: The thrombolysis in myocardial infarction (TIMI) risk score is calculated as the sum of independent predictors of mortality and ischemic events in ST elevation acute myocardial infarction (STEMI). Several studies show that the neutrophil to lymphocyte ratio (NLR) is a prognostic inflammatory marker. In preliminary studies, platelet to lymphocyte ratio (PLR) has been proposed as a pro-thrombotic marker. The relationship between NLR, PLR and TIMI risk score for STEMI has never been studied. Aim: To evaluate the association between TIMI-STEMI risk score and NLR, PLR and other biochemical indices in STEMI. Material and methods: In this retrospective study, we evaluated 390 patients who presented with STEMI within 12 h of symptom onset. Patients were grouped according to low and high TIMI risk scores. Results: We enrolled 390 patients (mean age 61.9 ±13.6 years; 73% were men). The NLR, platelet distribution width (PDW) and uric acid level (UA) were significantly associated with a high TIMI-STEMI risk score (p = 0.016, p = 0.008, p = 0.030, respectively), but PLR was not associated with a high TIMI-STEMI risk score. Left ventricular ejection fraction was an independent predictor of TIMI-STEMI risk score. A cut-off point of TIMI-STEMI score of > 4 predicted in-hospital mortality (sensitivity 75%, specificity 70%, p < 0.001). We found that NLR, PDW, and UA level were associated with TIMI-STEMI risk score. Conclusions: Neutrophil to lymphocyte ratio, PDW and UA level are convenient, inexpensive and reproducible biomarkers for STEMI prognosis before primary angioplasty when these indicators are combined with the TIMI-STEMI risk score. We believe that these significant findings can guide further clinical practice.